Hematocrit, hemoglobin and red blood cells are associated with vascular function and vascular structure in men - Kishimoto, Shinji; Maruhashi, Tatsuya; Kajikawa, Masato; Matsui, Shogo; Hashimoto, Haruki; Takaeko, Yuji; Harada, Takahiro; Yamaji, Takayuki; Han, Yiming; Kihara, Yasuki; Chayama, Kazuaki; Goto, Chikara; et al. (Scientific reports, 2020)
High and low hematocrit (Hct) and hemoglobin (Hb) levels are associated with the risk of cardiovascular disease. The purpose of this study was to determine the relationships of Hct, Hb and red blood cells (RBCs) with vascular function and structure. We measured flow-mediated vasodilation (FMD), nitroglycerin-induced vasodilation (NID), brachial intima media thickness (IMT), and brachial-ankle pulse wave velocity (baPWV) in 807 men. The subjects were divided into six groups according to the levels of Hct, Hb and RBCs. NID was highest in the 46.0–48.9% Hct group among the six groups according to Hct levels. Brachial IMT was lowest in the 46.0–48.9% Hct group among the six groups. There were no significant differences in FMD and baPWV among the six groups. We used 46.0–48.9% Hct as a reference to define the lower tertile. The adjusted odds ratio of being in the low tertile of NID was significantly higher in the < 42.9% and ≥ 49.0% Hct groups. Adjusted odds ratio of being in the low tertile of brachial IMT was significantly lower in the < 39.9% Hct groups. Similar results were obtained for Hb and RBCs. Low and high levels of Hct, Hb and RBCs were associated with vascular smooth muscle dysfunction, and low Hct levels were associated with abnormal vascular structure. Increases in the levels of Hct, Hb and RBCs within normal ranges may have beneficial effects on the vasculature.